Price discovery in currency markets - Carol Lee Osler; Alexander Mende; Lukas Menkhoff (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
This paper makes three contributions to our understanding of the price discovery process in currency markets. First, it provides evidence that this process cannot be the familiar one based on adverse selection and customer spreads, since such spreads are inversely related to a trade?s likely information content. Second, the paper suggests three potential sources for the pattern of customer spreads, two of which rely on the information structure of the market. Third, the paper suggests an alternative price discovery process for currencies, centered on inventory management strategies in the interdealer market, and provides preliminary evidence for that process.
Keywords: G14; F31; G15; 330; Bid-ask spread; foreign exchange; asymmetric information; microstructure; price discovery; interdealer; inventory; market order; limit order